Heterostructures design for Hf-Nitride/V-Nitride system. (December 2015) - Caicedo, J.C.; Escobar, C.; Aperador, W.; Caicedo, H.H.; Prieto, P.
Abstract: The multilayered films were grown via reactive r.f. magnetron sputtering technique by systematically varying the bilayer period ( Λ ) and the bilayer number ( n ), while maintaining constant the total coating thickness ( 2.4 μm) on silicon(100) substrates. The multilayers were characterized through high-angle X-ray diffraction (HA-XRD), low-angle X-ray diffraction (LA-XRD), HfN and VN layers were analyzed via X-ray Photoelectron Spectroscopy (XPS) and electron and transmission microscopy (TEM). The HA-XRD results showed preferential growth in the face-centered cubic (111) crystal structure for HfN/VN multilayer systems with the (111)[100]HfN //(200)[100]VN epitaxial relation. The maximum coherent assembly was observed with presence of satellite peaks. Highlights: Deposition pressure effect on chemical, morphological and optical properties. Multilayers system with the epitaxial relation (111)[100]HfN //(200)[100]VN . Coherent assembly progress with relevant optical properties. Dispersion coefficient, index of refraction for HfN/VN in relation to bilayer thickness.